2014
DOI: 10.1088/0004-637x/794/2/107
|View full text |Cite
|
Sign up to set email alerts
|

A New Cepheid Distance Measurement and Method for NGC 6822

Abstract: We present a revised distance to the nearby galaxy NGC 6822 using a new multi-band fit to both previously published and new optical, near-and mid-infrared data for Cepheid variables. The new data presented in this study include multi-epoch observations obtained in 3.6 µm and 4.5 µm with the Spitzer Space Telescope taken for the Carnegie Hubble Program. We also present new observations in J, H and K s with FourStar on the Magellan Baade telescope at Las Campanas Observatory. We determine mean magnitudes and pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…The slope of the nonlinear fit, and in turn, the reddening is mainly constrained by shorter wavelength B-, V-and I-band mean magnitudes. This "star-by-star" multi-wavelength, reddening and true distance modulus plot was first introduced by Rich et al (2014) in their parallel study of Cepheids in NGC 6822 (see their Figures 5 and 6). The difference in the dispersion when moving from optical to NIR measurements is due to intrinsic and extrinsic effects.…”
Section: Redime: a New Approach To Estimate Reddening Distance And Mementioning
confidence: 99%
“…The slope of the nonlinear fit, and in turn, the reddening is mainly constrained by shorter wavelength B-, V-and I-band mean magnitudes. This "star-by-star" multi-wavelength, reddening and true distance modulus plot was first introduced by Rich et al (2014) in their parallel study of Cepheids in NGC 6822 (see their Figures 5 and 6). The difference in the dispersion when moving from optical to NIR measurements is due to intrinsic and extrinsic effects.…”
Section: Redime: a New Approach To Estimate Reddening Distance And Mementioning
confidence: 99%
“…In many ways NGC 6822 resembles a two times less massive version of the SMC (e.g., Jameson et al 2016), except that the SMC is currently undergoing a strong interaction with the LMC and the Milky Way. The proximity ( =  D 474 13 kpc; Rich et al 2014) makes NGC 6822 an ideal target to study cloud structure and star formation at high resolution; at this distance,  » 1 2.3 pc, so that ALMA easily resolves cloud substructure. Like other comparatively isolated dwarf irregular galaxies, NGC 6822 is rich in gas with an atomic gas mass 11 of »Ḿ 1.3 10 atom 8  M (Weldrake et al 2003;de Blok & Walter 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…McAlary et al (1983) found E B−V = 0.36 mag, Gieren et al (2006) reported a similar average reddening of E B−V = 0.36 ± 0.01 mag. Rich et al (2014) used optical and infrared data for Cepheids to determine that the foreground reddening along the line of sight to NGC 6822 is E B−V = 0.35 ± 0.04 mag.…”
Section: Reddeningmentioning
confidence: 99%
“…NGC 6822 is a dark matter dominated (Weldrake et al 2003) dwarf irregular galaxy in the Local Group at a distance 476 ± 44 kpc (Rich et al 2014). It provides a low-metallicity environment compared to the majority of Local Group novae: [Fe/H] ≈ −0.5 (see, e.g., Larsen et al 2018).…”
Section: Introductionmentioning
confidence: 99%